A Blockchain Interoperability Framework to Streamline Information Sharing for Achieving Sustainability Outcomes - Chandan, Anulipt (Curtin University, 2023)
Consumers are increasingly concerned about the sustainability of the food they consume, but finding reliable information is often difficult. To tackle this problem, this research identified 30 sustainability indicators and created a blockchain system to provide trustworthy information to consumers. This enables consumers to make informed choices, while also helping companies build trust and improve customer satisfaction. With this sustainability information readily available, consumers can have peace-of-mind knowing they are making environmentally friendly choices.